Plan para la Dirección del Proyecto Remodelación y Construcción de las Instalaciones del Puesto Policial de Guardacostas, Moín - Corrales-Rodríguez, Ana Elena (Instituto Tecnológico de Costa Rica, 2013)
This project was created with the purpose of carrying out a Plan for Remodeling RECOPE is a state company that handles the import, processing and distribution of hydrocarbons for 45 years. RECOPE provides about 70% of the energy the country needs for its economic and social activities. The vision and mission of this company are focused on ensuring efficient supply of oil to the domestic market, taking into account customer satisfaction. The problems experienced by the Refinery Building Department with projects is that projects planned this does not meet the objectives in terms of time, cost, scope and quality. This was because there is no proper management and project management. This was done using the techniques of expert judgment, interviews with professional staff, head of the Building Department and others involved Refinery direct the Department to know how projects are undertaken. That is why this project was created with the purpose of carrying out a Plan for Remodeling Project Management and Construction of Facilities Since the Police Coast Guard, Moin, which will serve as the basis to achieve standardization in the Department of Building Refinery taking the basics of PMI. The structure of the plan is based on the planning, monitoring and control and close, taking the 8 carriers of knowledge as defined in the PMI. Not included in the scope of groups of processes of initiation and execution since the beginning of the project is due to a directive from the Presidency of Recope and the execution because Recope is a public entity is governed by the Act Administrative contracting so they hired the developer of the project in its implementation phase. Neither took into account the area of knowledge acquisition because it has a department Recope Procurement who are responsible for contracting and procurement and contractor in the execution takes over the supply of materials, equipment and labor used in the project. This plan is aimed primarily manage and facilitate the verification of each of the elements that must contain the proper management of projects and their respective directors. The main recommendations that were raised for this Plan, as part of the work are. With the implementation of this Plan for Remodeling Project Management and Construction of Facilities Since the Police Coast Guard, Moin, intended to make an evidence to the Department of Construction of the importance and ease of planning projects under the guidelines of PMI. It is recommended the Executive Chairman of Recope that since the beginning of the project was formally assigned a manager and a project team, which will maintain continuity in project development and establishment of clearer responsibilities.
Proyecto de Graduación (Maestría en Gerencia de Proyectos). Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos, 2012.
Keywords: Gestión de proyectos; Administración; Planificación